2019
DOI: 10.1002/adfm.201902467
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, Highly Stretchable, Rehealable, Sensing, and Fully Recyclable Ionic Conductors Fabricated by One‐Step Polymerization Based on a Small Biological Molecule

Abstract: To date, various stretchable conductors have been fabricated, but simultaneous realization of the transparency, high stretchability, electrical conductivity, self-healing capability, and sensing property through a simple, fast, cost-efficient approach is still challenging. Here, α-lipoic acid (LA), a naturally small biological molecule found in humans and animals, is used to fabricate transparent (>85%), electrical conductivity, highly stretchable (strain up to 1100%), and rehealable (mechanical healing effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(143 citation statements)
references
References 54 publications
2
126
1
Order By: Relevance
“…Dang et al. synthesized a series of highly stretchable ionic conductors by constructing hierarchical networks containing disulfide bonds, which possess excellent mechanical healing efficiency, 86 % recovery (tensile strength in the range 47–152 kPa) after re‐healing for 14 h at 25 °C, and could be fully reprocessed into new conductors by a direct heating process [7a] . Methacrylate copolymers with dual sulfide–disulfide cross‐linked networks, developed by An et al., displayed rapid self‐healability for 0.5–30 min at room temperature [9a] .…”
Section: Introductionmentioning
confidence: 99%
“…Dang et al. synthesized a series of highly stretchable ionic conductors by constructing hierarchical networks containing disulfide bonds, which possess excellent mechanical healing efficiency, 86 % recovery (tensile strength in the range 47–152 kPa) after re‐healing for 14 h at 25 °C, and could be fully reprocessed into new conductors by a direct heating process [7a] . Methacrylate copolymers with dual sulfide–disulfide cross‐linked networks, developed by An et al., displayed rapid self‐healability for 0.5–30 min at room temperature [9a] .…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that the hydrogels had shaped a stable network and exhibited predominant elastic solid performances. [ 33 ] The gradual augment of G ′ and G ′′ with the frequency increasing from 0.1 to 100 rad s −1 , which may on account of the relaxation effect of hydrogen bonds. [ 40 ] Besides, G ′ of the DN‐hydrogel with β‐CD 3.5% reached the highest.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the expensive nanomaterials, relatively complicated and time‐consuming fabrication processes are also significant limiting factors facing these stretchable conductors. [ 46,47 ] These problems encouraged researchers to seek other directions, such as polymer blends and ionic conductors for preparing self‐healing sensing components.…”
Section: Self‐healing Sensing Materials and Design Strategiesmentioning
confidence: 99%
“…It is worth mentioning that, although not defined explicitly as green sensing materials and devices, many reported examples are innately green and ecofriendly. [ 46,107,127,128 ] Nature has always been a source of inspiration for developing new functional materials. Therefore, turning to existing biological systems and materials that combine both degradability and self‐healing capabilities is highly attractive.…”
Section: Advanced Sensing Platforms Features and Applicationsmentioning
confidence: 99%